Design of reinforced concrete walls with openings for strength and ductility - Wu, Hui (2008)
[THIS THESIS CONSISTS OF THREE (3) PARTS - To date limited research on the seismic behavior of walls with irregular openings has been conducted, and a general design recommendation based on the strut-and-tie models and the capacity design procedures has been provided by the ACI 318 [AI] and NZS 3101 [N6] codes. However, the behavior of the structural walls with irregular openings subjected to seismic loadings and the details of the design procedures have not been adequately addressed. Therefore, experimental and analytical studies on the seismic design of walls with irregular openings were performed in this study.